"Brothers Under the Bridge": Factors Influencing the Transience of Registered Sex Offenders in Florida. (December 2015) - Socia, Kelly M.; Levenson, Jill S.; Ackerman, Alissa R.; Harris, Andrew J.
The transience of registered sex offenders (RSOs) is a major impediment to reentry success, particularly because it has been linked to increased absconding and recidivism, and thus decreased community safety. Unfortunately, there is limited existing research on what factors most influence this transience. The purpose of this study was to identify and explore the relative influence of factors predicting transience for RSOs. Using data gathered from the Florida sex offender registry and multiple supplemental state and federal data sources, the analysis revealed a number of county- and individual-level characteristics that are associated with the likelihood of RSO transience. At the county level, these include residence restriction coverage, housing affordability, and population density. At the individual level, these include age, minority status, victim type (minor vs. adult), risk level, supervision status, and prior failure to register convictions. Implications for policy and practice are discussed.